Predictors of nurses’ response to informal carers’ interventions in medication safety and their collaboration with nurse colleagues and physicians: a cross-sectional factorial survey from Switzerland / Prädiktoren der Reaktion von Pflegefachpersonen auf Interventionen von betreuenden Angehörigen zur Medikationssicherheit und ihre Zusammenarbeit mit pflegerischem und ärztlichem Personal: eine faktorielle Querschnittstudie aus der Schweiz - Riguzzi Marco (Sciendo, 2021)
Informal carers contribute significantly to healthcare delivery in Switzerland. Many of them are experienced in everyday practice and perform medication management procedures. Medication is a vital topic in patient safety; however, there is little knowledge about carers’ involvement in the medication process.